Critical Thinking Ability of German Literature Departement’s Students of Universitas Negeri Malang in Writing Thesis - Primardiana Hermilia Wijayati; Ferina Aulia Lestari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2021)
This article is a research result which aims to uncover the critical thinking skills of students of German Literature Department, Universitas Negeri Malang (UM) in writing thesis. The method used is qualitative content analysis with a coding sheet as an instrument. The data is taken from some chapters in German thesis, to be particular the background, the discussion, and the conclusion sections. The collected data is reduced, grouped, then the emerging patterns are analyzed and conclusions are drawn. Students' critical thinking skills in writing thesis were analyzed from four cognitive abilities (analysis, synthesis, evaluation, and argumentation) and nine cognitive standards (clarity, clarity, accuracy, precision, relevance, depth, breadth, logic, significance, and fairness). The results showed that students' critical thinking skills were good in the aspects of analysis, synthesis, and evaluation. However, from the argumentation aspect, students’ critical ability is still considered weak, because they produced errors in ethos, logos and pathos arguments, still made incomplete structures, and did not meet the criteria for critical thinking/cognitive standards of breadth and depth.